2011 IEEE/RSJ International Conference on Intelligent Robots and Systems 2011
DOI: 10.1109/iros.2011.6048757
|View full text |Cite
|
Sign up to set email alerts
|

Toward automatic classification of chemical sensor data from autonomous underwater vehicles

Abstract: Autonomous underwater vehicles (AUVs) are commonly used to support oceanographic science by providing water-column mapping, seafloor bathymetric and photographic survey, and deep-sea exploration capabilities. In practice, the mapping activities carried out by AUVs consist of flying either pre-programmed tracklines (most propeller-driven AUVs), or else reporting data to human operators at regular intervals that permit retasking (typical for month-long underwater glider deployments). AUVs equipped with the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore, water velocity measurements obtained with the DVL on Sentry, showed that the water currents at 1100m matched the direction of the plume measured with the mass spectrometer and provided information on the total hydrocarbon flux contained within the plume. The scientific findings of this expedition are reported in [5] and [15] reports additional results on the classification of chemical sensor data obtained on these dives.…”
Section: A June 2010 Oil Spill Response Cruisementioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, water velocity measurements obtained with the DVL on Sentry, showed that the water currents at 1100m matched the direction of the plume measured with the mass spectrometer and provided information on the total hydrocarbon flux contained within the plume. The scientific findings of this expedition are reported in [5] and [15] reports additional results on the classification of chemical sensor data obtained on these dives.…”
Section: A June 2010 Oil Spill Response Cruisementioning
confidence: 90%
“…Two additional expeditions are planned for this year -the first to investigate naturally occurring methane seeps off of California and the second will use magnetic measurements to estimate the age of the Western Pacific tectonic plate. In addition, we are continuing to advance both the sensor payload and autonomy of the vehicle [15]. These efforts are not just focused on oceanography but, through an award from NASA, also on using Sentry missions as analogues for astrobiological exploration [6], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Other environmental sensors mounted that have been used on AUVs include sheet lasers [75], fluorometers [15], mass spectrometers [36], optical backscatter sensors [100], and magnetometers [88]. If a prior map of su cient resolution is available, these environmental sensors can be used to navigate within the map.…”
Section: Challenges In Underwater Navigationmentioning
confidence: 99%
“…While prior 3D mapping of the site provides a solution to the navigation problem by creating occupancy grids, enabling online obstacle avoidance and path planning, complex operations often require an analysis of the 3D map by a human operator to identify the elements of interest and the potential hazards [9]. This intervention considerably increases the operation time and stress on the human operator.…”
Section: Introductionmentioning
confidence: 99%